Application of 5G innovative technology in the internal logistics of the iron and steel enterprise - Puyang ZHANG (Dianxin kexue)
With the development of the digital economy, the application of 5G in the industry has attracted increasing attention.How to make 5G bring tangible benefit improvement is an important research topic.The applications of 5G innovative technology in the internal logistics of the iron and steel enterprise area were taken as the research object, the needs of the industry were analyzed, and feasible application scenarios were proposed.The application landing situation of a logistics enterprise was mainly summarize.Opinions on the further expansion of application scenarios were put forward.The results indicate that the application of 5G innovative technology has significantly improved corporate efficiency.Useful ideas for the promotion and application of 5G in the industry were provided.